PENGARUH HARGA PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA APLIKASI TIKTOK SHOP (Studi Kasus Mahasiswa Program Studi Pendidikan Ekonomi) - Nukuhehe, Julyanti; Tupamahu, Kevin H; Tomasoa, Theodora F (Kupna Akuntansi: Kumpulan Artikel Akuntansi, 2025)
Product prices and promotions are important factors that can increase the purchase decision of students of the Economics Education Study Program. This study aims to determine the influence of product prices and promotions on purchase decisions on the TiktokShop application. The sample of this study is 96 TikTokShop users in the Economics Education Study Program. Data processing was carried out using SPSS version 25 with validity tests, classical assumption tests, multiple linear regression tests and hypothesis tests. Based on the results of the tests carried out, it was concluded that product prices and promotions partially or simultaneously had a positive effect on purchase decisions on TikTokShop. The influence given is quite large, namely 44.6%.